南極海における低気圧性および高気圧性渦の沈降粒子フラックスに及ぼす影響 - 三瓶, 真; 飯田, 高大; 真壁, 竜介; 成田, 篤史; 片山, 智代; 佐々木, 洋; Sampei, Makoto; Iida, Takahiro; Makabe, Ryusuke; Narita, Atsushi; Katayama, Tomoyo; Sasaki, Hiroshi (2014)
conference object